Stranger in paradise a Jesse Stone novel - Parker, Robert B., 1932-; Naughton, James, 1945-; Random House Audio Publishing (New York, NY : Random House Audio, 2008)
Apache hit man, Wilson "Crow" Cromartie returns to Paradise after ten years to take Amber Francisco back to her father in Florida, but before returning he is suppose to kill her mother Fiona. It's up to police chief Jesse Stone to provide protection to them.
Read by James Naughton.
Unabridged.
Compact discs.
3 7 13 17 19
Keywords: Stone, Jesse (Fictitious character) -- Fiction; Police -- Massachusetts -- Fiction; Kidnapping -- Fiction; Police chiefs -- Fiction; Massachusetts -- Fiction